2018
DOI: 10.21511/bbs.13(4).2018.10
|View full text |Cite
|
Sign up to set email alerts
|

The credit channels of monetary policy transmission: implications on output and employment in Nigeria

Abstract: There has been an increasing trend in the unemployment rate despite the growth rate witnessed. Monetary policy is presumed as one of the ways to improve the situation. Likewise, the relationship between monetary policy and employment has generated controversial debates in the literature. Though its connection has been extensively studied, however, the implications of monetary policy in respect to time frame perspectives on employment and output have not been widely addressed in the literature. This study provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Therefore, informed the niche of this study. Likewise, most African countries are regarded as low-income countries when high unemployment rate and poverty are the major macroeconomic problems [29][30][31]. Hence, Sphenostylis stenocarpa can help to improve the nutritional quality of these resource-poor countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, informed the niche of this study. Likewise, most African countries are regarded as low-income countries when high unemployment rate and poverty are the major macroeconomic problems [29][30][31]. Hence, Sphenostylis stenocarpa can help to improve the nutritional quality of these resource-poor countries.…”
Section: Introductionmentioning
confidence: 99%
“…These goals are particularly relevant for African countries, which have higher percentage of youth population being unemployed (IMF, World Economic Outlook, 2018). Nigeria has abundant human and natural resources but it still faces numerous developmental challenges such as high poverty rate, high unemployment rate and low income per capita (Popoola, Asaleye & Eluyela, 2018;Asaleye, Olurinola, Oloni & Ogunjobi, 2017;Asaleye, Popoola, Lawal, Ogundipe & Ezenwoke, 2018). One of the reasons attributed to low productivity growth, according to some scholars, is low rate of investment in human capital, another reason is the inability to know the right channel of human capital investment to embark on (Li, Lai, Wang & Zhao, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The results of their study revealed that monetary policy has no long-run relationship with economic activity and credit channel was not effectual in the transmission of monetary policy, while money supply, exchange rate, and interest rate channels were positive channels of monetary policy transmission. However, the findings that credit channel was not effectual in the transmission of monetary policy is doubtful and in contrast to the credit channel dominance in Nigeria, as revealed by Emenike (2017), Asaleye et al (2018). The omission of the short term lending rates in the model may be a specification error that was responsible for this.…”
Section: Literature Reviewmentioning
confidence: 90%
“…A few of these studies in Nigeria are the research work of Obafemi and Ifere (2015) and Osundina, Tella and Adesoye (2018) who found interest rate channel as the strongest channel of monetary policy to the real sector. Some found exchange rate channel as the strongest (Adekunle, Baba, Stephen, Ogbuehi, Idris and Zivoshiya, 2018); some found asset price channel as the strongest and others found credit channel as the strongest (Emenike, 2017;Asaleye, Popoola, Lawal, Ogundipe and Ezenwoke, 2018). Therefore, there is no clear consensus among the authors till date as to the main channel of monetary policy transmission to the Nigerian real sector.…”
Section: Introductionmentioning
confidence: 99%